Sistem Pemantauan Kehadiran Menggunakan Layanan Berbasis Lokasi Web di Kantor Desa Lumban Dolok - Harisanul Arifin; Suendri Suendri; Imam Adlin Sinaga (LPPM Universitas Sains dan Teknologi Komputer, 2026)
Employee attendance is an important indicator to demonstrate the discipline and performance of village employees. The process of recording employee attendance previously at the Lumban Dolok Village Office was still done manually. This can cause problems such as incorrect data, slow report collection, and absenteeism. Therefore, the purpose of this study is to develop a web-based presence-monitoring information system that uses the Location-Based Service (LBS) method. The purpose of the LBS method is to ensure that the attendance process can be carried out only when employees are within a specified radius of the Lumban Dolok Village Office. This system uses latitude and longitude data from the user's device to calculate the geographic distance to the location's center point. The developed system uses the user's device's latitude and longitude to calculate the distance between the employee's location and the attendance center. Within a radius of 25 meters, the attendance process can only be carried out if the employee is within that radius; if they are outside the radius, then the attendance will be automatically rejected by the system. In this study, the waterfall system development method was employed, with PHP and UML. The results of the study show that this system can help the village office monitor employee attendance directly, speed up the collection of attendance reports, and reduce the risk of data manipulation. In addition, attendance reports are easily accessible by admins and village heads to assess employee performance. Thus, the web-based attendance information system using the LBS method is expected to improve compliance, transparency, and effectiveness of attendance management at the Lumban Dolok Village Office.